The Utilization of E-Commerce and QRIS as Digital Payment Tools to Improve Sales Performance through Competitive Advantage in MSME - Nanang Wahyudin; Novita Herlissha; Christianingrum Christianingrum; Dwi Rizki Aldiesi (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2022)
The national contribution of MSMEs in supporting economic growth did not only occur during the 1998 monetary crisis but also during the COVID-19 pandemic in Indonesia. The pandemic also impacts economic activity, which causes every business actor to be able to create a competitive advantage in his business. In 2020 the President of Indonesia assigned his cabinet to prioritize the potential of the digital economy to drive economic growth. With competitive digitalization, MSMEs utilize information technology through e-commerce and support Bank Indonesia in accelerating the digitization of the payment system as the implementation of the Indonesian Payment System Blueprint (BSPI) 2025 through the Quick Response Code Indonesia Standard (QRIS). This study aims to determine whether using e-commerce and QRIS as digital payment tools can affect or improve the sales performance of MSMEs in Belitung through competitive advantage. This research used quantitative with a survey approach of 150 respondents. The study's results partially show that e-commerce and QRIS positively and significantly affect sales performance and competitive advantage. The results of the study simultaneously showed that the F-value was greater than F-table (52.220 > 3.02), and the probability was significant (p< 0.05). The simultaneous usage of e-commerce and QRIS significantly affects the sales performance of MSMEs in Belitung through competitive advantage.